Genome-wide analysis for genomic alteration in acute promyelocytic leukaemia - Hassan, Rosline (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2017)
Acute Promyelocytic Leukemia (APL) is a subset of acute myeloid leukemias (AML), and is commonly associated with the presence of chromosomal translocations leading to the expression of the PML-RARA fusion protein. Although chromosomal translocation has been implicated in leukemogenesis, other underlying mechanisms such as copy number variation (CNV), microRNA (miRNA) expression and gene expression may also play important roles in the pathogenesis of APL. In this study, we performed CNV analysis, FL T3 mutation analysis, miRNA expression profiling and gene expression-pathway based analysis to understand the underlying mechanism of genomic alteration involve in contributing to the different survival in subgroups of acute promyelocytic leukaemia patients. In CNV analysis, chromosomal deletion on subband 5q13.2, 8p23.1 and 16p 12.3 were commonly seen in six of eight cases (75%) and gain of 2p 11.2 and 14q32.33 were found in all cases (n=8). Mutational analysis of FLT3 genes did not show any significant finding in all patients samples. Global miRNA profiling was performed on APL samples by using the microarray approach, followed by Nanostring nCounter system to validate the results. MiRNA expression profiles from nCounter platform revealed that miR-1 00 is most significantly upregulated in APL patients as compared to normal controls. We identified most differentially expressed genes in RAS signaling pathway, MAPK, Apoptosis and JAK STAT signaling pathway of APL at diagnosis patients. In conclusion, this study showed that other underlying mechanisms also play important roles In the pathogenesis of APL. These findings provide new insights into the role of miRNAs and mRNA in the genetic origins of APL and highlight their potential as biomarkers for disease stratification and drug-targeted therapy.